2005
DOI: 10.1128/mcb.25.11.4782-4791.2005
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Precedes Chromatin Modifications under the Influence of the Strain-Specific Modifier Ssm1

Abstract: Ssm1 is responsible for the mouse strain-specific DNA methylation of the transgene HRD. In adult mice of the C57BL/6 (B6) strain, the transgene is methylated at essentially all CpGs. However, when the transgene is bred into the DBA/2 (D2) strain, it is almost completely unmethylated. Strain-specific methylation arises during differentiation of embryonic stem (ES) cells. Here we show that Ssm1 causes striking chromatin changes during the development of the early embryo in both strains. In undifferentiated ES ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
1
20
1
Order By: Relevance
“…The HRD transgene is in active chromatin in Ssm1d adults, but heterochromatic in adult Ssm1b mice (Padjen et al, 2005). In undifferentiated ESCs of both strains, the transgene is in a chromatin state intermediate between active and inactive.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The HRD transgene is in active chromatin in Ssm1d adults, but heterochromatic in adult Ssm1b mice (Padjen et al, 2005). In undifferentiated ESCs of both strains, the transgene is in a chromatin state intermediate between active and inactive.…”
Section: Introductionmentioning
confidence: 99%
“…This intermediate state is still observed in both B6 and D2 ESCs 1 week after removal of leukemia inhibitory factor (LIF) and feeder fibroblasts, except that in B6 the HRD transgene becomes associated with the methylated DNA-binding protein Mecp2. After differentiation in culture, in B6 ESCs HRD is heterochromatic, whereas in D2 the HRD transgene assumes an active chromatin state (Padjen et al, 2005). HRD transgenic RNA is expressed in D2 in all stages, but in B6 only in undifferentiated ESCs and during the first 3.5 days after differentiation in culture.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, direct binding of DNMT3a and DNMT1 to HDAC1 was observed (Fuks et al, 2000;Fuks et al, 2001), and histone methylation is also coupled with methylated human Alu elements (Kondo and Issa, 2003). Although many studies have suggested that DNA methylation may act as a primary player in silencing target genes preceding other epigenetic pathways (Hashimshony et al, 2003;Padjen et al, 2005;Schubeler et al, 2000), there are also scenarios where DNA methylation seems to act as a secondary event to stabilize gene silencing status initiated by existing chromatin modifications (Bachman et al, 2003;Mutskov and Felsenfeld, 2004;Tamaru and Selker, 2001). Studies on the kinetics of silencing of transgenes show that loss of histone acetylation and H3-K4 methylation is the first step leading to reversible transcriptional repression, which is followed by H3-K9 methylation and promoter DNA methylation to stabilize the silenced chromatin state (Mutskov and Felsenfeld, 2004).…”
Section: Dna Methylationmentioning
confidence: 99%